2022
DOI: 10.1002/jsfa.11964
|View full text |Cite
|
Sign up to set email alerts
|

Rapid identification of the geographic origin of Taiping Houkui green tea using near‐infrared spectroscopy combined with a variable selection method

Abstract: BACKGROUND Most studies focus on the geographically larger production areas in tea traceability. However, famous high‐quality tea is often produced in a narrow range of origins, which makes traceability a challenge. In this study, Taiping Houkui (TPHK) green tea of narrow geographical origin was rapidly identified using Fourier‐transform near‐infrared (FT‐NIR) spectroscopy. RESULTS First, spectral information of 114 TPHK samples from four production areas was acquired. Second, the synthetic minority over‐sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Results showed that the GA-BP model achieved the highest accuracy of 96.6% in discriminating coal mine dust wettability, followed by PSO-ELM, ELM, and BP models. Ge et al [30] collected 114 samples of Taiping Monkey Kui green tea from four production areas, establishing SNV-ELM and SNV-GA-ELM models based on the combination of near-infrared spectroscopy and chemometrics to accurately identify green teas from specific geographic origins. The ELM model combined with SNV preprocessing achieved an accuracy of 93.07%, while the ELM model after SNV preprocessing combined with GA feature variables achieved an accuracy of 95.35% for the test set.…”
Section: Extraction Of Characteristicsmentioning
confidence: 99%
“…Results showed that the GA-BP model achieved the highest accuracy of 96.6% in discriminating coal mine dust wettability, followed by PSO-ELM, ELM, and BP models. Ge et al [30] collected 114 samples of Taiping Monkey Kui green tea from four production areas, establishing SNV-ELM and SNV-GA-ELM models based on the combination of near-infrared spectroscopy and chemometrics to accurately identify green teas from specific geographic origins. The ELM model combined with SNV preprocessing achieved an accuracy of 93.07%, while the ELM model after SNV preprocessing combined with GA feature variables achieved an accuracy of 95.35% for the test set.…”
Section: Extraction Of Characteristicsmentioning
confidence: 99%
“…The spectral curves of these samples show the typical plant characteristics of green tea, which are consistent with our early work and those spectra measured by commercial instruments in other studies. [40][41][42][43][44][45][46] The reduction of spectral sampling points would result in the decrease of identification accuracy, which also reflects in the smoothness of the curves. Fortunately, we found that a spectral resolution of 10-20 nm is sufficient for the qualitative analysis of sugar-adulterating green tea in our previous work, and the characteristic bands mainly fall into 1300-1700 nm.…”
Section: Spectral Acquisition Of Adulterated Teamentioning
confidence: 99%
“…The tea industry is important for achieving rural revitalization and consolidating poverty alleviation results in many regions of China (Hu et al., 2022). Taiping Houkui tea, produced in the Huangshan region of Anhui Province, China, is characterized by two leaves embracing a bud, flat and straight shape, and hidden white fuzz (Jin et al., 2022; Liu et al., 2023; Zhou et al., 2022). The processing technology of Taiping Houkui is unique.…”
Section: Introductionmentioning
confidence: 99%